(3CUhd GdOjfs - (3jMji Hf GdMSjf Hf GdbGSe Hf EHQGgje GdMSfj GdYdhqj GdQSj, GdeYQha H GdgGOj pEdi GdnMqb, J (B298 (3g` s
(3ChdgG (B:s
(3SCdJ jG Hfi agec Gddg hfaYc YeG jOjf Gddg Hg , hdG JSY GMOkG ef Gdecdajf LgdI ef eYQaI GdGUhd s
(3BNQgG (B:s
(3hGdeYGHOg ddUOb cGf Gddg MSHg hhdi CeQg hddMGce HjffG hHjfg hgh NjQG GdMGcejf , JeJ GdGUhd s
(3GLGH GdeDda Ydi SDGd hLgI Gdjg GdSjO GHQGgje Hf GdeMSf GdYdhis
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
Keywords: (3eJaQbGJs